Effect of Vortex Finder Wall Thickness on Internal Flow Field and Classification Performance in a Hydrocyclone - Zaihai Wu; Zhitao Liang; Peiyang Li; Feng Li; Huanbo Yang (Separations, 2025)
The hydrocyclone generally exhibits limited separation efficiency and classification sharpness. As the discharge channel for fine particles, the vortex finder plays a critical role in influencing the classification performance through its structural parameters. However, the influence of vortex finder wall thickness on fly ash classification within the hydrocyclone has not yet been reported. In this study, computational fluid dynamics (CFDs) were employed to investigate the variations in pressure field, velocity field, and separation efficiency with respect to changes in vortex finder wall thickness. The results indicate that the radial velocity increases with vortex finder wall thickness, which facilitates the rapid formation of a particle-size stratification, thereby reducing the number of misclassified particles. The cut size initially decreases and then increases as the wall thickness of the vortex finder increases. A minimum cut size of 17.2 µm was observed when the wall thickness reached 10 mm. The classification sharpness improves progressively with increasing wall thickness. At a wall thickness of 15 mm, the steepness index reaches 0.68. Experimental results demonstrate that a thick-walled vortex finder structure can significantly enhance the classification sharpness of the hydrocyclone. Specifically, the content of −19 µm particles in the underflow decreased by 32.17% when the vortex finder wall thickness increased from 5 mm to 15 mm. Meanwhile, the proportion of −19 µm particles in the overflow increased by 12.72%. Therefore, employing a thick-walled vortex finder structure can not only enhance the cut size precision but also effectively improve the classification performance of the hydrocyclone.